Analisis Perhitungan Harga Pokok Proses Di Pabrik Tahu UD Ping Jaya Kupang - Tahu, Maria Yonita; Reinha Madia, Mariza Alfanda; Putri Jhonny, Melani; Lodang Manuk, Patrcia; Arlinda Dethan, Risni; Usfunan, Reyfenston; Jenanut, Skolastika; Maristha Serang, Syallomita; Bembot, Theresia Arthamevia; Leonisa Gasper, Theresia; Elfrida Owa, Yuliana (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2025)
This study aims to calculate the Cost of Goods Sold (COGS) at the UD Ping Jaya Tofu Factory using the process costing method. This method is used because the production process is mass-produced, repetitive, and produces a homogeneous product. Production cost data for October 2025 includes raw material costs of Rp111,000,000, direct labor costs of Rp17,000,000, and factory overhead costs of Rp28,520,000, resulting in a total cost of Rp156,520,000. The calculation was performed using equivalent units and cost per unit. The results show equivalent units of 10,400 kg for raw materials, 10,160 kg for direct labor, and 10,240 kg for overhead, based on 10,000 kg of finished product and 400 kg of work-in-process product. The COGS obtained is Rp15,131.44 per kilogram. Raw material costs are the largest component, contributing 70.9% of total costs. These results provide an accurate basis for the company in determining selling prices and controlling costs, while also proving that the process costing method is effectively applied at UD Ping Jaya. Keywords: Cost of Goods Sold, Cost of Goods Sold, Production Cost, Equivalent Units, Tofu Factory.